Penilaian returns investasi saham dengan Augmented Three Factor model pada kondisi political uncertainty di Indonesia - Rika Rahayu; Mar'atus Zahro (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
This study aims to analyze the market factor portfolio beta, small minus big portfolio beta, high minus low portfolio beta, market volatility beta portfolio effect on investment returns with the Fama and French augmented three factor model in the manufacturing industry under conditions of political uncertainty. This research is a quantitative research with the hypothesis that there is an effect of market factor portfolio beta, small minus big portfolio beta, high minus low beta portfolio, market volatility beta portfolio on investment returns with the Fama and French augmented three factor model in the manufacturing industry under political conditions uncertainty. The variables used in this study include the dependent variable, namely investment returns and the independent variables include market factor portfolio beta, small minus big beta portfolio, high minus low portfolio beta, market volatility portfolio beta. The measurement results with small minus big and market volatility have an effect on stock returns, while high minus low and market factors have no effect on investment returns. This study only focuses on the assessment of investment returns with the augmented three factor model of the Fama and French models, so for future researchers it would be better if they could use another model as a comparison.